Moths in selected forestal fringes of Agusan Marsh, Bunawan, Agusan del Sur - Dinampo, Kristy June G. (2009)
Opportunistic sampling was done for an inventory of the moth species in the selected forestall fringes of Agusan Marsh, Bunawan, Agusan del Sur. During the 14- month period of study, 45 species of moths were reckoned from the three different sampling sites (6 species in Kaliloan, 16 species in Mambalili, and 27 species in Tagbayangbang). The moth families classified were Archtiidae (Kaliloan-2; Mambalili-2; Tagbayangbang-3), Geometrodae (Tagbayangbang-1), Lasiocampidae (Tagbayangbang-1), Limacodidae (Mambalili-2; Tagbayangbang-5), Lymantriidae (Kaliloan-1; Mambalili-1; Tagbayangbang-1), Noctuidae (Mambalili-2; Tagbayangbang-4), Pyralidae (Mambalili-3; Tagbayangbang-1) Saturniidae (Tagbayangbang-1), Sphingidae (Mambalili-2; Tagbayangbang-2), Uraniidae (Mambalili-2; Tagbayangbang-3) and unidentified species (Kaliloan-1; Mambalili-3; Tagbayangbang-3)